Dakwah dan Pesan Akhlak Habib Husein Ja’far Al Hadar Dalam Membina Generasi Z Melalui Akun Youtube - Zidansyah, Arif; Soiman (Dakwah, 2024)
This research aims to analyze the moral messages conveyed by Habib Husein Ja'far Al Hadar in building the character of Generation Z through the YouTube channel "Jeda Nulis". The research method employs a qualitative approach with content analysis technique to identify, analyze, and evaluate the moral messages conveyed in his videos. The analysis will focus on the moral values, ethics, and life perspectives emphasized by Habib Husein Ja'far Al Hadar in the contemporary context relevant to Generation Z. The findings of this research are expected to provide a deeper understanding of Habib Husein Ja'far Al Hadar's efforts in nurturing the character and morality of Generation Z through the YouTube platform, as well as its impact in shaping positive behaviors and attitudes among today's youth. Thus, this research contributes to a broader understanding of the influence of social media and spiritual figures in shaping moral values among the younger generation.